First step in pre-miRNAs processing by human Dicer - Flores-jasso, Carlos Fabián (Nature Publishing Group, 2009)
AIM: To investigate the strand preference of the initial cleavage of human pre-miRNAs by human Dicer in vitro. METHODS: We used a series of in vitro transcribed pre-miRNAs that were radioactively labeled at their 5′ or 3′ ends in cleavage reactions with recombinant human Dicer or HeLa cytoplasmic S100 extracts. Pre-miRNAs samples were purified by denaturing and native PAGE and only the stem-loop structures were used in the experiments. Products of cleavage reactions were resolved by denaturing PAGE, and scanned by phosphor-imaging. RESULTS: Recombinant hDicer performs a biased first-cleavage in the pre-let-7b and hsa-pre-miR-17 3′ strand. This result is recapitulated in HeLa S100 cytoplasmic extracts. CONCLUSION: The differential first-nick is observed in cleavage reactions only when stem-loops are substrates for hDicer.